2019
DOI: 10.1200/jco.18.00545
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Trastuzumab and Docetaxel in Patients With Human Epidermal Growth Factor Receptor 2–Positive Salivary Duct Carcinoma

Abstract: Purpose Clinical evidence demonstrating the effectiveness of systemic therapy for advanced salivary duct carcinoma (SDC) is lacking because of the disease’s rarity. We assessed the efficacy and toxicity of trastuzumab plus docetaxel in patients with locally advanced and/or recurrent or metastatic human epidermal growth factor receptor 2–positive SDC. Patients and Methods This was a single-center, single-arm, open-label, phase II study in Japan. The patients received trastuzumab at a loading dose of 8 mg/kg, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
159
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(183 citation statements)
references
References 30 publications
1
159
1
5
Order By: Relevance
“…Although this is unusual, it is known from comparative studies that this may occur . Recently, preliminary data for 45 patients with HER2‐positive advanced unresectable SGC (of the ductal subtype) treated with docetaxel and trastuzumab in a phase 2 trial showed promising results, that is, overall response rate of 69%, median PFS of 11.3 months and median OS of 38.0 months . These results seem to support treating HER2‐positive SDC patients with trastuzumab plus docetaxel.…”
Section: Discussionmentioning
confidence: 96%
“…Although this is unusual, it is known from comparative studies that this may occur . Recently, preliminary data for 45 patients with HER2‐positive advanced unresectable SGC (of the ductal subtype) treated with docetaxel and trastuzumab in a phase 2 trial showed promising results, that is, overall response rate of 69%, median PFS of 11.3 months and median OS of 38.0 months . These results seem to support treating HER2‐positive SDC patients with trastuzumab plus docetaxel.…”
Section: Discussionmentioning
confidence: 96%
“…Besides ADT, other treatment options are available for patients with R/M SDC. In the case of ERBB2 (HER2) gene amplification (29.4–46.4%), patients can be treated with docetaxel plus trastuzumab, showing an overall response rate of 70.2% and median PFS of 8.9 months . Double HER2 blockade with docetaxel–trastuzumab–pertuzumab or in second‐line with the antibody‐drug conjugate trastuzumab‐emtansine also showed promising results .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ERBB2 (HER2) gene amplification (29.4-46.4%), 1,2 patients can be treated with docetaxel plus trastuzumab, showing an overall response rate of 70.2% and median PFS of 8.9 months. 8 Double HER2 blockade with docetaxel-trastuzumab-pertuzumab or in second-line with the antibody-drug conjugate trastuzumab-emtansine also showed promising results. [9][10][11] Finally, the high frequency (61.3%) of oncogenic driver gene mutations offers personalized treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in some cases, beneficial effects were found when either carboplatin/docetaxel or CAB was administered and followed by the other after PD. In addition, we have also reported on the treatment with trastuzumab/ docetaxel in 57 patients with HER2-positive SDC and observed an ORR of 70% (7). All patients with SDC included in the current study were HER2negative; thus, the two studies cannot be compared due to the different molecular backgrounds.…”
Section: Discussionmentioning
confidence: 93%
“…We have previously reported an SDC classification system for the selection of an appropriate and personalized systemic therapy with anti-HER2, anti-AR, and/or cytotoxic drugs (26). We have also recently reported two prospective studies of anti-AR and anti-HER2 therapy that were based on this classification system (6,7). In a phase II study of CAB in 36 patients with AR-positive SGC, including 34 cases of SDC, an ORR of 42% was observed (6).…”
Section: Discussionmentioning
confidence: 99%